How Hope Defi(n)es South Africa: Reimagining Hope in Johannesburg’s Slovo Park Beyond State Failures - Eileen Jahn (The February Journal)
This article examines the dual role of hope in South Africa, highlighting its power as both a transformative force and a constraining burden amid systemic state failures and persistent socio-economic inequalities. Drawing on President Cyril Ramaphosa’s rhetoric of hope as a cornerstone of national identity and resilience, it explores how hope operates politically and affectively in a society shaped by historical adversity, political disillusionment, and ongoing infrastructural crises. Focusing ethnographically on the Slovo Park informal settlement in Johannesburg, the article reveals how residents navigate government rhetoric, exposing hope’s paradoxical role—offering resilience while also fueling frustration. While state-sponsored hope has served as a tool of governance and social cohesion, its failure to deliver tangible change has led marginalized communities to redefine hope on their own terms. Engaging with literature on hope as both an aspirational force and a mechanism of control, this article argues that hope sustains belief in progress but also constrains agency when institutional failures persist. Shifting focus from state rhetoric, it highlights how marginalized communities reconstruct hope as a grassroots tool for change—transforming it into a source of agency, resilience, and self-determined action, and reclaiming its potential to drive meaningful change. This analysis contributes to broader debates on hope’s role in perpetuating systemic inequalities while also offering a means for reclaiming its power to drive meaningful change in post-apartheid South Africa.